The ability to analyze the latest market trends in increasing sales in MSMEs Bouqetcru - Sahabuddin, Romansyah; Ibrahim Rauf , Deddy; Putri, Saza Ghadiza; Nurlina, Nurlina; Muchtar, Muh Farhan; Ilmi, Humairah Nurul; Sulfikar, Muhammad Fahrul (Junal Ilmu Manajemen, 2024)
The title of this research is the ability to analyze the latest market trends in increasing sales for small and medium-sized businesses. This research was conducted to find out which marketing strategies apply to Bouqetcru SMEs, what market trends are used by Bouqetcru SMEs, and how influential the marketing strategies and current market trends are used by Bouqetcru SMEs. The method used in this research is a qualitative research method using this type of research whose instruments are interviews and documentation. The research results support this strategy, Coupon marketing can increase sales of Bouqetcru MSME products, thus marketing strategies really need to be considered and developed by following existing market trends for future business sustainability. Umkm Bouqetcru is developing a marketing strategy by joining the online sales arena by taking advantage of market trends, namely celebrity endorsements and promotions on the Instagram platform.